Impact of social media on the continuous education of the general surgeon, a new experience, @Cirbosque: A Latin American example (2020)
ocial media has gained widespread recognition for its importance in the medical field. Such platforms play an important role for learning and teaching, because knowledge can be transmitted instantly and massively, and specialists in different world-wide locations can discuss experiences instantaneously. The present article presents our experience of using social media to facilitate surgical learning while encouraging leadership and global mentoring. This retrospective descriptive study was initiated at the time of the creation of our social media handle on Twitter, February 22, 2019. Since that time, we have posted 10,587 academic tweets; the monthly growth rate has been 9% (393 new followers per month). Currently, we have 4,213 followers, 11,241,000 impressions, 121,105 visits, and 121,105 mentions. We have reviewed 59 topics of interest in general surgery and 132 clinical cases in trauma, as well as in hepatobiliary, gastrointestinal, thoracic, and acute-care surgery. We have made 13 image challenges using illustrations of diagnostic and intraoperative images. Although the evidence is uncertain to promote education performed entirely through social media, we show that @Cirbosque has been effective, and the impact of this initiative on Twitter is appreciated by many surgeons worldwide, including renowned teachers in each of the topics addressed. Furthermore, the number of participants in the discussions increased each day, as did all impact indicators according to Twitter Analytics. Thus, we conclude that the educational message of @Cirbosque is having a positive effect and reaching thousands of people worldwide, suggesting that others can develop similar outreach programs in education and communication.